Pain Therapy Guided by Purpose and Perspective in Light of the Opioid Epidemic - Severino, Amie L.; Shadfar, Arash; Hakimian, Joshua K.; Crane, Oliver; Singh, Ganeev; Heinzerling, Keith; Walwyn, Wendy M. (Frontiers in Psychiatry, 2018)
Prescription opioid misuse is an ongoing and escalating epidemic. Though these pharmacological agents are highly effective analgesics prescribed for different types of pain, opioids also induce euphoria, leading to increasing diversion and misuse. Opioid use and related mortalities have developed in spite of initial claims that OxyContin, one of the first opioids prescribed in the USA, was not addictive in the presence of pain. These claims allayed the fears of clinicians and contributed to an increase in the number of prescriptions, quantity of drugs manufactured, and the unforeseen diversion of these drugs for nonmedical uses. Understanding the history of opioid drug development, the widespread marketing campaign for opioids, the immense financial incentive behind the treatment of pain and vulnerable socioeconomic and physical demographics for opioid misuse give perspective on the current epidemic as an American-born problem that has expanded to global significance. In light of the current worldwide opioid epidemic, it is imperative that novel opioids are developed to treat pain without inducing the euphoria that fosters physical dependence and addiction. We describe insights from preclinical findings on the properties of opioid drugs that offer insights into improving abuse-deterrent formulations. One finding is that the ability of some agonists to activate one pathway over another, or agonist bias, can predict whether several novel opioid compounds bear promise in treating pain without causing reward amongst other off-target effects. In addition, we outline how the pharmacokinetic profile of each opioid contributes to their potential for misuse and discuss the emergence of mixed agonists as a promising pipeline of opioid-based analgesics. These insights from preclinical findings can be used to more effectively identify opioids that treat pain without causing physical dependence and subsequent opioid abuse.